2009
DOI: 10.1039/b813957c
|View full text |Cite
|
Sign up to set email alerts
|

Detection of drugs and their metabolites in dusted latent fingermarks by mass spectrometry

Abstract: A hydrophobic silica dusting agent containing carbon black has been used with latent finger marks to demonstrate that the agent can act as an enhancing matrix to generate a simple method for detecting a range of drugs using surface assisted laser desorption/ionisation time-of-flight mass spectrometry (SALDI-TOF-MS) in positive ion reflectron mode. The dusting agent produces developed marks for locating/visualising the prints whilst also acting as a SALDI-TOF-MS enhancer that is equivalent to the standard matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
97
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 18 publications
2
97
0
4
Order By: Relevance
“…In addition, the use of SALDI-TOF-MS enabled the detection of EDDP, a major metabolite of methadone, together with its parent drug in the same fingermark from an individual taking methadone [16]. As methadone is taken as an oral dose, it was concluded that the presence of the parent drug in the fingermark arises from its secretion from the blood in the same manner as for metabolites.…”
Section: Application Of the Ceia For The Analysis Of Latent Fingermarksmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the use of SALDI-TOF-MS enabled the detection of EDDP, a major metabolite of methadone, together with its parent drug in the same fingermark from an individual taking methadone [16]. As methadone is taken as an oral dose, it was concluded that the presence of the parent drug in the fingermark arises from its secretion from the blood in the same manner as for metabolites.…”
Section: Application Of the Ceia For The Analysis Of Latent Fingermarksmentioning
confidence: 99%
“…In addition, Rowell et al were able to show isolated patches of cocaine contamination in a fingerprint obtained from an individual being treated at a drug addiction centre using surface assisted laser desorption/ionisation time-of-flight mass spectrometry (SALDI-TOF-MS). The non-homogenous pattern of cocaine contamination in the print was thought to be due to the subject's fingertip coming into contact with the drug prior to the time of sampling [16]. Analytical methods for the detection of these types of cocaine residues in latent fingermarks could be used in a forensic context, as their presence would provide further evidence of a suspect's involvement in drug use or trade.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As an exemple, desorption electrospray ionization (DESI) MS has been successfully applied to several exogenous substances and external uptake detection [17]. Surface assistedlaser desorption/ionization-time-of-flight (SALDI-TOF) MS has been carried out for the detection of some fatty acids, dehydrated cholesterol, squalene, as well as the identification of explosives, drugs, and nicotine residues [8,18,19]. More recently, matrix-assisted-laser desorption/ionization (MALDI) TOF MS has been reported for the detection of endogenous substances, such as amino acids, fatty acids, peptides, dehydrated cholesterol, squalene, DAGs, and TAGs, as well as surfactants, polymers, drugs, pharmaceuticals, and explosives [20][21][22].…”
Section: Introductionmentioning
confidence: 99%